2019
DOI: 10.1002/jaba.647
|View full text |Cite
|
Sign up to set email alerts
|

A translational evaluation of renewal of inappropriate mealtime behavior

Abstract: The term renewal describes the recurrence of previously extinguished behavior that occurs when the intervention context changes. Renewal has important clinical relevance as a paradigm for studying treatment relapse because context changes are necessary for generalization and maintenance of most intervention outcomes. The effects of context changes are particularly important during intervention for pediatric feeding disorders because children eat in a variety of contexts, and extinction is an empirically suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…However, some authors have used different criteria for determining if renewal occurred. For example, in Case 66 described by Ibañez et al (), target responding increased during the fourth renewal‐test session and the authors described this as renewal despite responding being low during the three preceding renewal sessions. Liddon et al () did not describe this as renewal for a similar delayed effect in Case 23.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, some authors have used different criteria for determining if renewal occurred. For example, in Case 66 described by Ibañez et al (), target responding increased during the fourth renewal‐test session and the authors described this as renewal despite responding being low during the three preceding renewal sessions. Liddon et al () did not describe this as renewal for a similar delayed effect in Case 23.…”
Section: Discussionmentioning
confidence: 98%
“…Another difference between renewal studies using humans compared to nonhuman animals is that experiments are often conducted across calendar days wherein participants are exposed to different contexts and contingencies between and within experimental phases. Ibañez et al () indicated that their investigation of ABA renewal of inappropriate mealtime behavior took between 5 to 10 business days to complete and in their results indicated when a new day began. For the majority of participants, increases in inappropriate mealtime behavior were observed on the first session of a new day, both in the elimination phase (i.e., therapists implementing extinction) and in the reintroduction of the original context in the final phase (i.e., caregivers implementing extinction).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations